Pengaruh Komitmen Organisasi dan Disiplin Kerja terhadap Motivasi Serta Dampaknya terhadap Kinerja Aparatur Sipil Negara Pada Badan Pengelolaan Keuangan dan Pendapatan Daerah Provinsi Jambi - Paslah, Roni; Hapsara, Osrita; Akbar, Ali (J-MAS (Jurnal Manajemen dan Sains), 2024)
This study aims to obtain an overview of the influence of organizational commitment, work discipline, motivation and performance of state civil servants on the Regional Financial and Revenue Management Agency (BPKPD) of Jambi Province. To answer the research objectives, the researcher conducted literature observations related to several research variables, as well as reviewing relevant journals. The population of this research is all BPKPD Jambi Province employees totaling 166 employees. The population of this study was too large, so the researcher decided to use a sample taken based on the Slovin formula, where the error rate was 10%, and obtained a sample of 63 employees. Data analysis using the path analysis method to measure the influence of the research variables. The next analysis is R square and hypothesis testing (t test and F test). The research results show that both simultaneous and partial organizational commitment and work discipline have an influence on work motivation and performance. This indicates that the high level of organizational commitment and work discipline of employees at work can increase their work motivation, thereby having a positive effect on their performance. This research concludes that organizational commitment, work discipline, work motivation and employee performance at BPKPD Jambi Province are at a fairly high level. In addition, organizational commitment and work discipline, both simultaneously and individually, have a significant positive effect on work motivation and performance. Meanwhile, work motivation also has a significant positive effect on performance.Â